Preliminary Results with the AVR ImpaCt Frequency-Transposing Hearing Aid - McDermott, Hugh J.; Knight, Michelle R. (Journal of the American Academy of Audiology, 2001)
Currently, the only behind-the-ear hearing aid that provides a frequency transposition function is the ImpaCt DSR675, recently introduced by AVR Communications Ltd. of Israel. In tests with three hearing-impaired adults, the performance of the ImpaCt aid(s) was compared with that of each subject's own (nontransposing) hearing aids. Recognition of monosyllabic words and medial consonants did not differ significantly between the two types of aids. This suggests that the transposition function of the ImpaCt was not effective at providing these subjects with increased high-frequency speech information, at least for the programmable parameters applied in the experiments. However, the subjects' understanding of sentences in a competing noise was significantly poorer with the ImpaCt than with the subjects' own aids. In that test, the ImpaCt aids were programmed to attenuate parts of the noise. The decreased sentence recognition may have resulted from this program, which effectively reduced the bandwidth of the ImpaCt aids.Abbreviations: AGC = automatic gain control, ANOVA = analysis of variance, CFE = Clinician Fitting Environment, CNC = consonant-vowel nucleus-consonant, DCB = dynamic consonant boost, FCVL = frequency compression for voiceless sounds, HPF = high-pass filter, LPF = low-pass filter, SNR = signal-to-noise ratio
Keywords: Frequency transposition; hearing aids; speech perception